Kebahagiaan Dosen UIN Sunan Ampel Surabaya - Rizma Fithri (Indonesian Psychological Research, 2020)
Abstract : The purpose of this research to understand the picture of the happiness lecturer of civil servants and non-civil servants are there surroundings Islamic University of Sunan Ampel Surabaya country. The sample used as many as 75 of the subject lecturer of civil servants and non-civil servants, with random sampling techniques in 9 faculties. Data analysis techniques using descriptive statistics. The results of this study brings out the score's happiness of any professors of civil servants or non civil servants of 9 faculties, score range from number 1-6. Score 1-2 illustrates the level of happiness "was not happy"; score 2-3 illustrates the level of happiness "rather unhappy"; score 3-4 illustrates levels of happiness "very unhappy"; 4 describe the level of happiness "somewhat happy" score 4-5 illustrates the level of happiness "pretty happy"; score 5-6 illustrates the level of happiness "was very happy"; and 6 describe the level of happiness "too happy", as well as the analysis of the answers to open questions that have been answered by the subject. On the subject of civil servants, there are 8 subjects who have levels of happiness "very unhappy"; 6 subjects who have levels of happiness "somewhat happy"; 39 subjects who have levels of happiness "pretty happy"; and 1 subjects who have levels of happiness "very happy". While in a non civil servants, lecturers there are three subjects who have levels of happiness "very unhappy"; 3 subjects who have levels of happiness "somewhat happy"; and 15 subjects who have levels of happiness "quite happy". Keyword : Happiness, Lecturer at the Islamic University of Sunan Ampel Surabaya country